Progressive Web Application Development by Example: Develop Fast, Reliable, and Engaging User Experiences for the Web - Love, Chris (Packt Publishing, Limited, 2018)
Do you want to create amazing applications which grab the attention of users? Progressive web apps are just the right thing for you. With its example-based approach, this book will show you how effective progressive web apps can boost the performance of web and native apps.